UNRAVELING COMPLEXITY: ASSESSING THE IMPACT OF REAL EFFECTIVE EXCHANGE RATE ON UZBEKISTAN’S TRADE DYNAMICS - Gafurov Khurshid Maksudovich (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article investigates the complex interplay between economic theory and real-world trade dynamics in Uzbekistan, with a particular focus on the Real Effective Exchange Rate (RER). Contrary to conventional expectations, our findings reveal a negative correlation between export volume to Kazakhstan and RER changes, challenging the assumption that so’m depreciation consistently drives export growth. Additionally, a counterintuitive trend emerges in import dynamics, where the volume of imported goods consistently rises during periods of so’m depreciation, contradicting traditional theoretical predictions. Beyond RER, the study underscores the presence of unexplored factors shaping trade patterns.